ANALYSIS OF COOPERATIVE PERFORMANCE MEASUREMENT USING BALANCED SCORECARD: (STUDY ON EMPLOYEES COOPERATIVE HOSPITAL II SUBANG YEAR 2021) - Icih Icih; Asri Handayani; Kurnia Kurnia; Krisna Natanael (STIESA Press, 2022)
Performance measurement is one of the important factors that determine the success of a company in achieving goals. Initially, performance measurement only focused on financial performance, but it did not provide overall performance measurement results. Thus, a comprehensive and balanced performance measurement system is needed in the form of the Balanced Scorecard method as a company performance measurement system. The object of this study is the Subang II Hospital Employee Cooperative in 2021. This type of research is quantitative descriptive research. The variables in this study use perspectives in the balanced scorecard including financial perspectives, customer perspectives, internal business process perspectives, and learning and growth perspectives. The data used is secondary data from the Accountability Report of the Management and Supervisors in the 2020 and 2021 Annual Member Meetings of the Subang Ii Hospital Employee Cooperative. In addition, the secondary data used includes books and journals. The method of data collection is documentation. The results of this study show that the BSC score of the Subang II Hospital Employee Cooperative in 2021 with an overall score of 60%, which is a contribution from the financial perspective score of 36%, the customer perspective 4%, the internal business process perspective of 10%, and the learning and growth perspective of 10%. The results show that the performance of the cooperative has not been able to achieve the specified target.